Artificial oocyte activation using Ca2+ ionophores following intracytoplasmic sperm injection for low fertilization rate - Akashi, Kazuhiro; Yamada, Mitsutoshi; Jwa, Seung Chik; Utsuno, Hiroki; Kamijo, Shintaro; Hirota, Yasushi; Tanaka, Mamoru; Osuga, Yutaka; Kuji, Naoaki (Frontiers in Endocrinology, 2023)
This large multi-center retrospective study examined whether artificial oocyte activation (AOA) using Ca2+ ionophore following ICSI improves the live birth rate for couples with previous ICSI cycles of unexplained low fertilization rate. In this large-scale multi-center retrospective study conducted in Japan, data were collected from Keio University and 17 collaborating institutions of the Japanese Institution for Standardizing Assisted Reproductive Technology. Between January 2015 and December 2019, 198 couples were included in this study. Oocytes for both the intervention and control groups were procured from the same pool of couples. Oocytes obtained from ICSI cycles with no or low fertilization rate (<50%) with unknown causes were included in the control (conventional ICSI) group while oocytes procured from ICSI cycles followed by performing AOA were assigned to the intervention (ICSI-AOA) group. Those fertilized with surgically retrieved sperm were excluded. ICSI-AOA efficacy and safety were evaluated by comparing these two groups. Live birth rate was the primary outcome. The ICSI-AOA group (2,920 oocytes) showed a significantly higher live birth per embryo transfer rate (18.0% [57/316]) compared to that of the conventional ICSI group with no or low fertilization rate (1,973 oocytes; 4.7% [4/85]) (odds ratio 4.5, 95% confidence interval 1.6–12.6; P<0.05). A higher live birth rate was observed in younger patients without a history of oocyte retrieval. Miscarriage, preterm delivery, and fetal congenital malformation rates were similar between the two groups. ICSI-AOA may reduce fertilization failure without increasing risks during the perinatal period. AOA may be offered to couples with an ICSI fertilization rate < 50%.